A new perspective of mechanosensitive pannexin-1 channels in cancer metastasis： clues for the treatment of other stress-induced diseases - Wu, Di; Li, Lanfang; Chen, Linxi (Acta biochimica et biophysica Sinica, 2016)
Cancer metastasis is a process that cancer cells deviate from the primary site and spread to the other areas to form new colonies, which is the leading cause of death in cancer patients. During metastatic progression, circulating cancer cells lodge within the microvasculature of end organs, where most of them die from mechanical deformation.